Resilience characterization and evaluation model of field area network for the power distribution network - Fang XIAO; Shuyan YANG; Bo WEN; Xiaorong ZHU (物联网学报)
To analyze the robustness and reliability of field area network (FAN) in the power distribution network, a quantifiable network resilience characterization and evaluation model was proposed.The elasticity indicator was defined from network connectivity, robustness and redundancy, and the total network elasticity was calculated by the weighted sum.The resilience performance of FAN was evaluated by simulating random failures and malicious attacks.A single node failure was simulated and tested to evaluate the difference in network resilience a affected by different node failures and find the weak points of resilience in the network.The elastic characterization and evaluation model was extended to general network topologies, and simulation experiments were carried out using BA scale-free network and ER random network.The experimental results demonstrate the universality of the model.